Prevalencia de violencia de género en adolescentes del cantón Calvas - Reinoso Vallejo, Jimmy Alexander (2024)
Violence can be understood as an act of power of some over others and is It manifests itself through attacks that can be physical, verbal, psychological, economic, sexual, political, patrimonial, among others. The purpose of this study was to analyze the prevalence of gender violence in adolescents in the Calvas canton, type of study performed was descriptive, cross section; developed with a total population of 6378 adolescents whose ages range between 10 and 19 years; and, a sample of 144 people who They belonged to the educational establishments of the canton, corresponding to the levels of basic education and high school. The development of this degree work was carried out by applying surveys in person, by using the platform of Google forms, in he that HE attach a job of consent informed managed to the parentsof family I representatives legal of the teenagers, later to the awarded by the authoritiesinstitutional corresponding. Getting as results the following data: adolescents who suffer violence in the canton bald are 52%, being more prevalent in women between 10 and 14 years old, single marital status with 92%, mixed ethnicity with 88%, secondary education with 60% , whose occupation is described as student in 84% of the individuals analyzed. However the guy of violence that suffer these teenagers are mostly of guy physical followed by verbal and psychological violence, notably evidencing that within the Calvas canton the prevalence of Gender violence predominates more in the female gender, turning out to be a health problem public